2021
DOI: 10.1002/lno.11743
|View full text |Cite
|
Sign up to set email alerts
|

Role of small Rhizaria and diatoms in the pelagic silica production of the Southern Ocean

Abstract: We examined biogenic silica production and elementary composition (biogenic Si, particulate organic carbon and particulate organic nitrogen) of Rhizaria and diatoms in the upper 200 m along a transect in the Southwest Pacific sector of the Southern Ocean during austral summer (January–February 2019). From incubations using the 32Si radioisotope, silicic acid uptake rates were measured at 15 stations distributed in the Polar Front Zone, the Southern Antarctic Circumpolar Current and the Ross Sea Gyre. Rhizaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
(85 reference statements)
0
14
2
Order By: Relevance
“…Acantharea), provides substantial mineral ballast (Takahashi 1983) conferring them a key role in vertical export that is supported by their common presence in sediment traps (Bernstein et al 1987;Gutierrez-Rodriguez et al 2019;Michaels et al 1995;Preston et al 2020) and their enrichment in suspended and sinking particles (Duret et al 2020). Despite their abundance and their important role in biogeochemical processes (Biard et al 2016;Guidi et al 2016) little is known about the vertical distribution of Radiolaria particularly in the meso-and bathypelagic ocean (>500 m) (Biard and Ohman n.d.;Boltovskoy 2017;Llopis Monferrer et al 2021;Ollison et al 2021). In our study, we found an opposite distribution between Acantharea and RAD-B, which showed preference for the upper (<500 m) and deeper (>500 m) mesopelagic samples, respectively (Figure 7).…”
Section: /20mentioning
confidence: 99%
“…Acantharea), provides substantial mineral ballast (Takahashi 1983) conferring them a key role in vertical export that is supported by their common presence in sediment traps (Bernstein et al 1987;Gutierrez-Rodriguez et al 2019;Michaels et al 1995;Preston et al 2020) and their enrichment in suspended and sinking particles (Duret et al 2020). Despite their abundance and their important role in biogeochemical processes (Biard et al 2016;Guidi et al 2016) little is known about the vertical distribution of Radiolaria particularly in the meso-and bathypelagic ocean (>500 m) (Biard and Ohman n.d.;Boltovskoy 2017;Llopis Monferrer et al 2021;Ollison et al 2021). In our study, we found an opposite distribution between Acantharea and RAD-B, which showed preference for the upper (<500 m) and deeper (>500 m) mesopelagic samples, respectively (Figure 7).…”
Section: /20mentioning
confidence: 99%
“…The contribution of Rhizaria to the biogenic silica biomass can be highly variable. For example, in productive areas of the World Ocean, where Rhizaria are less abundant and diatoms concentrations are much higher, the impact of these protists on the biogenic silica biomass in surface waters is much lower, as in the case of the Ross Sea in Antarctica, where Rhizaria account for only 0.1% at most of the total biogenic silica (Llopis Monferrer et al, 2021).…”
Section: Comparison Of Imaging and Metabarcoding Resultsmentioning
confidence: 99%
“…There are a few ways to estimate the values of biogenic silica content of individual specimens. One way is by chemical analysis as performed by Llopis Monferrer et al (2020, 2021), another way is by mass measurement of only a few large (> 400 μ m) radiolarian species using an electronic precision balance and then take the average (Takahashi 1991) or using simple radiolarian skeleton models that combine geometrical shapes such as spheres, cones, cylinders, ellipsoids, and cuboids (Jacot Des Combes and Abelmann 2009). In fact, since the skeletons of radiolarians have a very complicated structure, they cannot be exactly reproduced with a simple geometric model.…”
Section: Figmentioning
confidence: 99%